Potency of Cell Wall Protein of Pasteurella multocida as Hemorrhagic Septicemia Vaccine on Swamp Buffaloes - Herliani Herliani; Abrani Sulaiman; M Ilmi Hidayat (Journal of Wetlands Environmental Management, 2020)
Vaccine candidate tests were carried out in the Laboratory of Microbiology, Faculty of Agriculture ULM; and the Laboratory of Molecular Genetics, Faculty of Science and Technology Airlangga University. The field test was conducted in Tampakang Village, Hulu Sungai Utara district and Bati-Bati village, Tanah Laut district that was including sterility test through vaccine mediated Brain Heart Infusion (BHI) inoculation. Safety testing was applied in experimental animals (mice and swamp buffaloes). Serum was tested serologically using Enzyme Linked Immuno Sorbent Assay (ELISA). Vaccine safety test showed 100% of mice and buffalo are surviving without clinical symptoms according to the characteristics of hemorrhagic septicemia disease. ELISA test indicated vaccinations increase antibody production, namely the Optical Density (OD) Æ› 450 Æžm 0.292 before vaccination to be 0.748 and 1.576 after vaccination and to be 1.821 after boosted. Based on sterilization test, safety test, and vaccine potency test, the vaccine candidate from cell wall proteins of P. multocida local isolate can be used to prevent hemorrhagic septicemia disease that infect swamp buffalo both on laboratory and field experiment.